Thermodynamics of the OWC chamber: Experimental turbine performance under stationary flow. (August 2020) - Moñino, A.; Quirós, C.; Mengíbar, F.; Medina-Lopez, E.; Clavero, M.
Abstract: Among the different devices designed to extract energy from waves, the Oscillating Water Column (OWC) operating an air turbine has been one of the most studied in recent years. The aim of this paper is to study the polytropic exponent associated to the thermodynamic process that takes place through the turbine in a non-idealised environment. A real gas model is applied, considering the influence of the moisture in the air chamber. Experimental data from a simplified OWC chamber set up under stationary flow are interpreted within the frame of an analytical real gas model. For that purpose, thermodynamic variables involved in the compression/expansion process have been calculated with the implementation of a real gas model. Following the results, in which differences between the ideal gas adiabatic polytropic process and the real gas model are observed, a new value for the polytropic exponent is proposed, representing a non–adiabatic real gas behaviour for the air–water vapour mixture. This approach allows a fine adjustment prediction of OWC performance, that can result more realistic in the case of OWC performance prediction under moderate wave climate conditions. From that on, new management guidelines can be developed, in which eventually moderate/low production prospects can be counterbalanced with more efficient and low–cost design. Highlights: Experimental study of an OWC chamber implementing a turbine under stationary flow. Assessment of the compression process under moistened air conditions. Study of the thermodynamics of the chamber process under real gas hypothesis. Analysis of polytropic exponent describing the OWC compression process for conditions other than ideal adiabatic.